Analyzing the Relationship between Corporate Governance and Financial Performance in BUMDs in Indonesia - Gitta Destalya Adrian Nova; Anis Feblin; Mardiah Kenamon; Yusi Inaya Putri (Universitas Bangka Belitung, 2023)
Abstract This study aims to determine the effect of budget participation, accountability accounting and motivation on managerial performance of regional water companies in Ogan Komering Ulu Regency. Research using a quantitative approach with primary data sources. The population was 200 employees, the sampling technique used random sampling as much as 25 percent of the population, by distributing questionnaires. The analysis technique uses multiple linear regression with hypothesis testing, namely partial test (t test) and simultaneous test (f test). The results in this study indicate that the variables of Budget Participation (X1), Accountability Accounting (X2) and Motivation (X3) have a significant effect on Managerial Performance (Y) of the Regional Drinking Water Company of Ogan Komering Ulu Regency both partially and simultaneously. The coefficient of determination (Adjusted R square) is 0.960, indicating that 96% of managerial performance variables at PDAM OKU Regency can be explained by the three independent variables. Keywords: Managerial Performance, Accountability Accounting, Budget Participation and Motivation.